Historical Perspectives on Erklr̃en and Verstehen - Feest, Uljana. (Archimedes, New Studies in the History and Philosophy of Science and Technology, 2010)
The conceptual pair of "Erklr̃en" and "Verstehen" (explanation and understanding) has been an object of philosophical and methodological debates for well over a century. Discussions <U+0013> to this day <U+0013> are centered around the question of whether certain objects or issues, such as those dealing with humans or society, require a special approach, different from that of the physical sciences. In the course of such philosophical discussions, we frequently find references to historical predecessors, such as Dilthey<U+0019>s discussion of the relationship between "Geisteswissenschaft" and "Naturwissenschaft", Windelband<U+0019>s distinction between nomothetic and idiographic methods, or Weber<U+0019>s conception of an interpretative sociology. However, these concepts are rarely placed in the historical contexts of their emergence. Nor have the shifting meanings of these terms been analyzed. The present volume considers a variety of intellectual, social, and material factors that contributed to the debate. Far from reducing the debates to their cultural and institutional contexts, however, the volume also offers careful systematic reconstructions of the arguments at hand, thereby enabling the reader to not only appreciate the situatedness of this exciting period of intellectual history, but also to reflect upon the current relevance of the various interpretations of the dichotomy between explanation and understanding.